Prioritizing Psychographics: Identifying Target Audience Segments’ Values for Strategic Climate Change Communications - Ginger Orton; Laura Morgan Fischer; Cara Lawson; Jessica Dammers Hemphill (Journal of Applied Communications, 2025)
Climate change communication poses a challenge for agricultural science communicators as the issue has become increasingly polarized in American society. Currently, the public has varying perceptions of climate change, its surrounding science, and divergent viewpoints of what should be done in response. With climate change’s impacts predicted to become more destructive, those interested in activating public climate support have examined efforts to understand how to most effectively engage the public with climate change messages. Target audiences have been identified as a necessary communication strategy when communicating about controversial topics, such as climate change, that incite strong internal reactions. Scholarship has called for increased attention to personal characteristics such as trust and values that may have stronger influences on message processing than other more commonly measured perceptions such as political ideology and perceived cause of climate change. We identified five strategic target audiences for tailored climate change communication based on survey data measuring participants’ climate change perception, trust in science, trust in media, and political ideology through a K-means cluster analysis. Then, we described the values and demographic profiles of each audience group to provide insight for strategic message development. Because certain values have been positively associated with certain climate behaviors, our results may guide and inform future value-congruent messaging efforts that consider target audience’s values, climate-related perceptions, and demographics. This study establishes a foundation for future experimental message testing research to build upon, which would answer the need for understanding how message characteristics influence target audiences.
Keywords: Audience Segmentation; K-means Cluster Analysis; Strategic Science Communication